Zum hundertjährigen Bestehen des Chinesisch-Deutschen Wörterbuchs von Werner Rüdenberg - Rink, Christian (Lexikographisch-grammatische Perspektiven.Tradition, Veränderung und Vielfalt in Lexikographie und Wörterbuchforschung Stefan J. Schierholz zum 70. Geburtstag, 2025)
The research field of bilingual lexicography for Chinese and German is still in its early stages. This paper serves as a starting point for further extensive metalexicographical research in this area. Rüdenberg’s 1924 Chinese-German Dictionary is considered the first widely available dictionary for both languages, introduced to the German public at the beginning of the twentieth century. This paper examines its history, reception, and lexicographic structures. The results indicate that, despite several defects and flaws, the dictionary stands among the great works of a largely imperialistic era – yet one that facilitated and ultimately normalized linguistic interaction between the inherently different languages of Chinese and those of the European continen
Keywords: bilingual lexicography Chinese/German; Werner Rüdenberg; dictionary analysis; dictionary structures